Relationship between Family Support and Anxiety Levels in Preoperative Appendix Patients at Rsi Malahayati Medan in 2022 - Muslimah Pase (Institute of Computer Science (IOCS), 2022)
Appendicitis is one of the most common cases in abdominal surgery which causes acute abdominal pain and requires immediate surgery to prevent complications which are generally dangerous. The purpose of this study is the Relationship between Family Support and Anxiety Level in Preoperative Appendix Patients at RSI Malahayati Medan in 2022. This study used a correlation description design, the population of this study was 25 people with a total sample of 25 people with accidental sampling technique. Data obtained through the Family Support questionnaire. The data was processed using the Chi Squere test and presented in the form of a frequency distribution table. Research results obtained influence with a significance value or sig. (2-tailed) of 0.000<0. The conclusion of this study is that there is a relationship between family support and anxiety levels in preoperative appendix patients at Malahayati Hospital. It is hoped that families will pay attention to the support given to patients who will be operated on.